2008
DOI: 10.1167/iovs.07-1643
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Polyol Pathway in High Glucose–Induced Apoptosis of Retinal Pericytes and Proliferation of Endothelial Cells

Abstract: ARI rescued pericytes from high glucose-induced apoptosis and maintained the levels of TGF-beta, resulting in the prevention of cocultured EC growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 43 publications
(36 reference statements)
1
26
0
1
Order By: Relevance
“…Sorbitol accumulation following polyol pathway activation reportedly promotes degeneration and apoptosis of several cell types in high glucose conditions (37). In our study, hyperglycemia promoted sorbitol accumulation followed by Schwann cell de-differentiation, which also occurs following peripheral nerve injury.…”
Section: Discussionsupporting
confidence: 58%
“…Sorbitol accumulation following polyol pathway activation reportedly promotes degeneration and apoptosis of several cell types in high glucose conditions (37). In our study, hyperglycemia promoted sorbitol accumulation followed by Schwann cell de-differentiation, which also occurs following peripheral nerve injury.…”
Section: Discussionsupporting
confidence: 58%
“…showing that pericytes are able to inhibit EC proliferation when co-cultured in direct contact [17,20]. However, those results were obtained with bovine or porcine cells, not human-derived cells.…”
Section: Discussionmentioning
confidence: 87%
“…Consequently, it is important to study their pathophysiological mechanisms in experimental contests where the interactions between these two cell types are preserved. Even though some studies in the literature used EC-pericyte co-cultures [16][17][18], in our knowledge this is the first time in which pericytes and EC of human origin have been utilized.…”
Section: Discussionmentioning
confidence: 99%
“…43 The selective loss of pericytes has been reported to be the hallmark of DR 44,45 and pericyte loss in dogs has been linked to AR activity 17,46,47 ; however, the selective loss of pericytes versus endothelial cells is controversial. [48][49][50][51][52] Using rat retinal capillary pericyte (TR-rPCT) and endothelial (TR-iBRB) cells, we have previously reported that short-term hyperglycemia results in pericyte apoptosis that is linked to the AR-catalyzed accumulation of sorbitol and that pericytes exposed to hypoglycemia demonstrate ER stress-linked apoptotic signaling. 53 More recently, Leal et al have reported that long-term hyperglycemia induces apoptosis in retinal endothelial (TR-iBRB) cells independent of caspase activation.…”
mentioning
confidence: 99%